The neutral real interest rate: An updated view of r* - Sara S. Meyer; Pål Ulvedal; Erik S. Wasberg (Norges Bank, 2022)
The neutral real rate of interest (r*) is a key variable for assessing the tightness of monetary policy. The neutral real interest rate has by all accounts fallen substantially over the past three decades, amid slowing productivity growth, an ageing population, increased inequality and increased demand for safe and liquid assets along with lower investment demand. Updated model estimates and long-term market rates support Norges Bank's assessment that the neutral real money market rate lays between -0.5 and 0.5 percent. Going forward, a further rise in life expectancy might suggest a continued very low r*, while increased public investment in defence and the climate transition, as well as the phasing out of asset purchase programmes by the large central banks may pull up on r*.
hdl:11250/3011212
Keywords: 330; monetary policy; neutral real rate of interest; r*